Acute Myeloid Leukemia (AML) With T-Cell Differentiation Arising From Chronic Myelomonocytic Leukemia (CMML) - Anthony Crymes; Mark G. Evans; Deepa Jeyakumar; Jerry J. Lou; Xiaohui Zhao; Sherif A. Rezk (Case Reports in Hematology)
Chronic myelomonocytic leukemia (CMML) is a myelodysplastic/myeloproliferative neoplasm characterized by peripheral blood monocytosis and bone marrow dysplasia. In approximately one-fourth of cases, CMML can demonstrate progression to acute myeloid leukemia (AML), referred to as AML ex CMML. We present a 58-year-old woman with a past medical history of idiopathic thrombocytopenic purpura (ITP) who demonstrated 24% bone marrow blasts on a repeat biopsy obtained two years after being diagnosed with CMML. By the flow cytometric analysis, the blasts expressed partial CD34, CD13, CD117, partial MPO, and partial CD123 with coexpression of the T-lymphoid markers CD2, CD5, CD7, partial CD4, cytoplasmic CD3, partial cytoplasmic TDT, and CD38, suggestive of AML with rare mixed myeloid/T-cell phenotype. Treatment with various agents including decitabine, cytarabine, daunorubicin, etoposide, and venetoclax, and two experimental bromodomain and extraterminal (BET) inhibitors did not produce sustained remissions, and the patient eventually succumbed to her disease. T-cell phenotype is an exceedingly rare feature of AML ex CMML, and whether this unique differentiation pathway contributed to the aggressive disease course remains unclear.